Modification of Proteins of Membrane-Cytoskeleton Complex During Cryopreservation of Human Erythrocytes at PEG-1500 Presence - Zemlyanskikh, N. G.; Zubov, P. M.; Babiychuk, L. A. (Problems of Cryobiology and Cryomedicine, 2008)
In the work there were investigated the modifications of protein content of membrane-cytoskeleton complex in erythrocytes exposed to PEG-1500 solution and cryopreserved under its protection in the media with different ionic strength and varying concentrations of bivalent ions. Peculiarities of erythrocyte protein spectra in membrane-cytoskeleton complex caused by PEG-1500 and low temperature were established.